Evaluation of Separate and Simultaneous Kinetic Parameters for Levulinic Acid and Furfural Production from Pretreated Palm Oil Empty Fruit Bunches - Misri Gozan; Jabosar Ronggur Hamonangan Panjaitan; Dewi Tristantini; Rizal Alamsyah; Young Je Yoo (International Journal of Chemical Engineering)
Palm oil empty fruit bunches (POEFBs) can be converted into levulinic acid (LA) and furfural, which are among the top building-block chemicals. The purpose of this study was to investigate separate and simultaneous kinetic model parameters for LA and furfural production from POEFBs, which were pretreated by soaking in aqueous ammonia (SAA). The highest LA yield, which was obtained at a reaction temperature of 170°C after 90 min in an acidic solution with a concentration of 1 M, was 52.1 mol%. The highest furfural yield was 27.94 mol%, which was obtained at a reaction temperature of 170°C after 20 min in an acidic solution with a concentration of 0.5 M. SAA pretreatment affected activation energy in glucose degradation reactions and favoured direct conversion of hemicellulose to furfural. The activation energy of LA production (EakHMF) increases with higher acid catalyst concentration, and the activation energy of furfural production (EakXYN) decreases with higher acid concentration. These trends in the activation energy occurred in both separate and simultaneous kinetic models. Simultaneous kinetic model is better to calculate kinetic parameters of LA and furfural production than separate kinetic models because the simultaneous kinetic model had a lower sum of square error (SSE) when estimating kinetic parameters.